Dampak Berbagai Pola Asuh terhadap Tingkat Obesitas Anak: Sebuah Tinjauan Literatur: The Impact of Diverse Parenting Styles on Childhood Obesity Rates: A Literature Review - Prasiefa, Maghfirahima Ghaniyyahusna; Muriana, Gendhis Rezki Kharim; Budiono, Anastasia Ivannia; Rahmania, Himma Aulia; Witanto, Icasia Izzah Rahmawati; Prasiefa, Mizanurafi’ Ghifarhadi (Universitas Airlangga, 2025)
Background: Childhood obesity is a growing global public health concern, affecting more than 20% of children and adolescents aged 5–19 years worldwide. This condition results from interactions among genetic, behavioural, and environmental factors. The family environment plays a crucial role in shaping children’s eating behaviours and self-regulation. Parenting style refers to general child-rearing approaches, whereas feeding practices describe specific parental strategies related to food. Distinguishing between these concepts is essential for understanding behavioural pathways associated with childhood obesity risk. Objectives: This review aimed to synthesise empirical evidence on the association between parenting styles and childhood obesity, as well as to examine the role of feeding practices and psychosocial factors as underlying mechanisms. Methods: A narrative literature review was conducted based on 27 articles published between 2015 and 2025. Studies were retrieved from PubMed, Web of Science, Scopus, and PsycINFO. The included studies employed cross-sectional and longitudinal designs involving children aged 4–18 years and assessed obesity-related outcomes, such as body mass index and eating behaviours. Discussions: Authoritative parenting was consistently associated with healthier dietary patterns and a lower risk of childhood obesity. In contrast, authoritarian, permissive, and uninvolved parenting styles were more frequently associated with an increased risk of obesity, although the strength of these associations varied. Non-responsive feeding practices, including excessive restriction and pressure to eat, were identified as important mediating mechanisms. Conclusions: Parenting style plays a significant role in shaping childhood obesity risk, both directly and indirectly through feeding practices and psychosocial pathways.